1987
DOI: 10.1007/bf02554950
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the penis by rectocolic adenocarcinoma

Abstract: A case report of a rectal carcinoma metastasizing to the penis is reviewed along with a total of 44 similar cases reported in the world literature. Pertinent arguments are presented in favor of yet another possible route of metastases, namely the perineural route, which has not been considered previously. Cavernosography provides valuable information about the extent of tumor spread; used more often, it would lead to recognition of the rare opportunity when an aggressive surgical approach might achieve prolong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…7 Penile metastases usually present on average 13 months after diagnosis of primary tumor and two-thirds have disseminated metastases at presentation. 1,2 The most common presenting symptoms in order are difficulty voiding, perineal pain, asymptomatic nodule and priapism. 1 The route of spread is contentious, but most authors favor retrograde venous spread from the pudendal venous system into the dorsal venous system of the penis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Penile metastases usually present on average 13 months after diagnosis of primary tumor and two-thirds have disseminated metastases at presentation. 1,2 The most common presenting symptoms in order are difficulty voiding, perineal pain, asymptomatic nodule and priapism. 1 The route of spread is contentious, but most authors favor retrograde venous spread from the pudendal venous system into the dorsal venous system of the penis.…”
Section: Discussionmentioning
confidence: 99%
“…1 The primary site of origin in order of frequency is bladder, prostate, rectum and recto sigmoid areas, and kidney. 1 Metastases to the penis from primary rectal tumors form an even smaller subgroup. A comprehensive literature review revealed only 35 cases occurring in the setting of a rectal primary carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, by removing two cases where metastases appeared in the 9th and 26th year [2,3] after the primary treatment, the average onset of penile metastases was 25 months. Two-thirds of the patients had disse-minated metastases at presentation [4]. Occasionally, penile metastases can be a synchronous finding [5,6], or present as a leading symptom of the disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…Total penectomy remains the only treatment to have shown a longer-term survival in patients with localized disease [7]. Surgery might also have a role in palliation where there is intractable penile pain [4].…”
Section: Discussionmentioning
confidence: 99%